Mind Regained - Pols, Edward (Cornell University Press, 1998)
In this highly accessible book, a distinguished philosopher says current focus on the brain conceals the real powers of the mind. Edward Pols revisits one of the basic topics of philosophy: what is the distinction between mind and body and what is the relation between them? He disagrees fundamentally with the many contemporary philosophers who concentrate on the findings of neurophysiology and cognitive science and so look only to the brain for the causes and explanation of mind. Pols concedes the importance of such scientific studies but maintains that they focus on the infrastructure of mind and ignore the momentous difference between the infrastructure and mind itself.Pols calls upon the reader to attend to mind itself as a concrete and experientially available reality. This kind of attention, he argues persuasively, reveals mind to be at once causally dependent on the brain and causally effective on the physical processes of the brain and the world. Pols also examines the hierarchical view of mind and causality first proposed by Plato and Aristotle, the supersession of that view by the received scientific doctrine of causality, and the mistaken denial of the power of the mind to know an independent reality-a denial that resulted from the philosophical doctrines about knowing developed in the era that began with Descartes and ended with Kant